Paradoxical Frontalis Activation: An Underrecognized Consequence of Facial Palsy. Issue 2 (February 2018) - Cooper, Lilli; Izard, Charles; Harries, Victoria; Neville, Catriona; Venables, Vanessa; Malhotra, Raman; Nduka, Charles
Abstract : Background: Aberrant reinnervation and synkinesis are common and debilitating after facial palsy. Paradoxical frontalis activation can antagonize eye closure and increase the risk of corneal damage. If recognized, judicious botulinum toxin injection to the affected side may reduce this risk. Methods: One hundred consecutive patients with synkinesis were identified from a prospective database. Routine facial view photographs were converted to a standardized scale using iris diameter. The vertical distance from the midpoint of the midcanthal line to the inferior border of the eyebrow was measured bilaterally. A value of p < 0.05 was considered significant. Results: Eighty-two patients were included, with a median age of 44 years (interquartile range, 33 to 59 years); 59 of the patients were women. The commonest cause was idiopathic ( n = 55). The median time since onset of palsy was 13 months (interquartile range, 6.5 to 27 months). There was less midpoint of the midcanthal line to the inferior border of the eyebrow excursion on the synkinetic side of the face ( p < 0.001). Twenty-two patients (27 percent) displayed paradoxical frontalis movement on the affected side of their face, with increased midpoint of the midcanthal line to the inferior border of the eyebrow distance (eyebrow raise) when attempting eye closure compared with eyebrow raise ( n = 19), and tight eye closure compared with gentle eye closure ( n = 3). Conclusions: This study highlights the phenomenon of paradoxical frontalis activation during eye closure. This is often underrecognized and may contribute to lagophthalmos. The authors found it to be present in 27 percent of patients with moderate or severe synkinesis. Further dynamic studies are required to understand the relationship among frontalis activity, eye closure, and the effects of its inhibition. Abstract : Supplemental Digital Content is available in the text.